An Analysis of the Use of Gadget on Students' Learning Outcome (Case Study) - Rachman, Arief Syaiful; Aniq KHB, Moh; Setianingsih, Eka Sari (Universitas Pendidikan Ganesha, 2020)
Most of the students use gadgets for playing games, social media, editing videos, watching YouTube. This study aims to determine the use of gadgets, the impact, and the learning outcomes of elementary school students. This type of research is qualitative research with research subjects namely fifth-grade students.Â The data obtained using observation, questionnaires, interviews, documentation. The results showed that 8 students used gadgets for more than 2 hours because they had personal gadgets, 2 students were hesitant and 8 students admitted that it was less than 2 hours per day which was mostly used for playing but sometimes used for studying. Gadgets have both positive and negative impacts, and from the results of the learning scores of the fifth-grade students during the middle of the semester, it can be seen from the eighteen students whose gadget users are in the quite good category because many students have an average score above Kkm, which is 70 with a value of 71. -86 and only three students who scored three students who got a grade below Kkm were 68-69. The results showed that the data on students' scores using personal gadgets were around eleven students, there were two children whose scores were below KM, namely 68 and 69, six children scored 71-79, and three children scored 82-86, the data of students who used gadgets owned by their parents around seven students scored 68 one student and six students scored between 71-79. Based on the results of the study, it can be concluded that male students' use of gadgets is more likely to play games, while female students tend to play social media more often and edit videos.